Zarys specyfiki zapożyczeń we współczesnym rosyjskim i polskim języku prawnym - Łuksza, Serafina (Acta Polono-Ruthenica, 2006)
The article focuses attention on the importance of the lexical borrowings in contemporary legal language. The research field covers Russian and Polish legal lexical systems. In both language systems one can observe the tendency to create more sophisticated specialized vocabulary, language globalization that is being expressed by creating parallel terms.